The Algorithmic Gaze: Deconstructing Authorship and Aesthetics in Generative Artificial Intelligence (AI) Art - Hesti Putri; Dais Susilo; Ervin Munandar; Hanifah Yasin; Idris Atmaja (Enigma in Cultural, 2025)
The proliferation of advanced text-to-image generative AI represents a paradigmatic shift in visual culture. It instigates a profound crisis for established concepts of authorship and aesthetics while also raising critical questions about artistic labor and the political economy of cultural production. This study investigates the complex negotiations between human creators and algorithmic systems. This study employed a qualitative, multi-modal methodology. A visual semiotic analysis was conducted on a curated corpus of 300 artworks from Midjourney, DALL-E 3, and Stable Diffusion, sampled to mitigate platform-specific biases. This was triangulated with a thematic analysis of semi-structured interviews with a purposive sample of 15 artists and designers actively using these tools. The methodological limitations, specifically the sample's "adopter-centric" bias, are explicitly acknowledged. The visual analysis identified a distinct "algorithmic gaze" characterized by hyper-compositing, surreal corporeal logic, and stylistic convergence, reflecting both the system's non-human perspective and the biases of its training data. The thematic analysis of artist interviews revealed three dominant experiential themes: the artist's role being reframed as curatorial, the creative process as a form of dialogue, and the interaction as an exploration of the system's "latent space". These participant narratives often frame the interaction in terms of empowerment and collaboration. In conclusion, generative AI reconfigures authorship into a distributed network phenomenon. However, this study argues that this posthuman collaboration occurs within a system structured by significant power asymmetries. The aesthetics of the algorithmic gaze are not neutral but are shaped by the commercial and ideological imperatives of the platforms. The artist's experience of empowerment coexists with broader material processes of deskilling, alienation, and the centralization of cultural production. Understanding this new paradigm requires a critical synthesis of posthumanist theory and political economy.